Application of Pediococcus acidilactici LUHS29 immobilized in apple pomace matrix for high value wheat-barley sourdough bread. (15th September 2017) - Bartkiene, Elena; Vizbickiene, Donata; Bartkevics, Vadims; Pugajeva, Iveta; Krungleviciute, Vita; Zadeike, Daiva; Zavistanaviciute, Paulina; Juodeikiene, Grazina
Abstract: The aim of this study was to evaluate the potential use of Pediococcus acidilactici LUHS29 immobilized in apple pomace in case to apply in barley sourdough fermentation for functional bread production. The strain was phenotypically characterized by the growth and acidification rate, carbohydrate metabolism and resistance to acidic conditions. The effect of immobilized bacterial cells on antioxidant properties of barley sourdough and on the acrylamide content in wheat-barley bread was analyzed. The phenotypic and molecular testing indicates the P. acidilactici having a versatile carbohydrate metabolism and acid resistance, showing 42.7% of viable cells surviving after incubation at low pH as compared to initial number (7.5 log10 CFU/g). Fermentation with immobilized strain increased by 15.3% the production of LA compared to spontaneous fermentation (24.2 g/kg), and the ability to producel -lactic acid contents up to 92.7% from the total LA. The use of P. acidilactici for barley sourdough fermentation increased β-glucan solubility by 1.3–5.1%, moreover, the total phenolic compounds (TPC) content and radical scavening activity were found higher up to 34.6% and 79.7%, respectively. Addition of barley sourdough at a level of 10% could reduce acrylamide content in bread up to 44% and retard bread staling process. The application of immobilized in apple pomace bacterial cells could have the future impact for the food industry due to the bioactive potential. Highlights: P. acidilactici LUHS29 has a versatile carbohydrate metabolism and acid resistance. Immobilization in apple pomace matrice supports the stability of bacterial cells during refrigerated storage. Fermentation of barley increased the bioactive potential of bread. Barley sourdough at a level of 10% reduces acrylamide content in bread and retards its staling process.